Advanced Electric Propulsion Diagnostic Tools at IOM. (2017) - Bundesmann, C.; Eichhorn, C.; Scholze, F.; Spemann, D.; Neumann, H.; Scortecci, F.; Leiter, H.J.; Holste, K.; Klar, P.J.; Bulit, A.; Dannenmayer, K.; Amo, J. Gonzalez del
Abstract: Recently, we have set up an Advanced Electric Propulsion Diagnostic (AEPD) platform[1], which allows for the in-situ measurement of a comprehensive set of thruster performance parameters. The platform utilizes a five-axis-movement system for precise positioning of the thruster with respect to the diagnostic heads. In the first setup (AEPD1) an energy-selective mass spectrometer (ESMS) and a miniaturized Faraday probe for ion beam characterization, a telemicroscope and a triangular laser head for measuring the erosion of mechanical parts, and a pyrometer for surface temperature measurements were integrated. The capabilities of the AEPD1 platform were demonstrated with two electric propulsion thrusters, a gridded ion thruster RIT 22 (Airbus Defence & Space, Germany, [13]) and a Hall effect thruster SPT 100D EM1 (EDB Fakel, Russia, [1, 4] ), in two different vacuum facilities.